Return on Assets, Debt-to-Equity Ratio, and Current Ratio on Firm Value with Firm Size as a Moderating Variable in Industrial Sector Companies Listed on the Indonesia Stock Exchange - Anti Hastuti UMP; Fuad Ramdhan Ryanto (Advances in Economics & Financial Studies, 2026)
Purpose: This study examines the associations of Return on Assets (ROA), Debt-to-Equity Ratio (DER), and Current Ratio (CR) with firm value and evaluates whether firm size moderates these relationships among Indonesian industrial companies. Research Method: The study uses a quantitative short-panel design comprising 110 firm-year observations from 55 industrial companies listed on the Indonesia Stock Exchange during 2023–2024. Firm value is measured using Price-to-Book Value. The revised analysis requires panel regression with centered interaction terms, firm and year effects, relevant controls, influence diagnostics, sensitivity analysis, and firm-clustered robust standard errors. Results and Discussion: Preliminary ordinary-regression estimates indicate positive associations of ROA, DER, and CR with firm value but provide no evidence that firm size moderates these relationships. These findings remain subject to confirmation using the revised panel specification. Implications: Managers should improve asset efficiency, maintain sustainable leverage, and manage liquidity productively. Investors should assess financial quality and risk rather than relying solely on corporate scale. Originality: The study evaluates firm size as a boundary condition linking financial ratios to the market valuation of Indonesian industrial companies.